Teacher Autonomy and Preferences in Professional Development: A Comprehensive Survey of Florida Educators - Unal, Zafer; Unal, Aslihan (Innovare Journal of Education, 2023)
Most educators around the world are required to participate in professional development activities in order to renew certification or licensure and ensure employees are up to standard. This study examined the professional development needs of 1,167 in-service teachers in Florida, United States, through a comprehensive survey. Findings revealed discrepancies between the current decision-making process for teachers’ professional development and their preferences. Teachers expressed a strong preference for autonomy in identifying their professional development needs, as well as a desire for more diverse formats, such as teacher observations and conference attendance. Additionally, the study found that teachers highly value professional development activities during designated days set aside by the school system and express interest in incorporating college or university settings into their experiences. The survey results also highlighted teachers’ preferences for effective professional development experiences, encompassing four key components: addressing what teachers need to know, demonstrating how to do it, suggesting best practices on implementation, and leaving time for specific questions. Furthermore, teachers demonstrated a clear understanding of their professional development needs, covering a range of topics such as effective teaching practices, classroom management, and integrating technology. Based on these findings, the study proposes a centralized professional development system, allowing teachers to input their needs and search for approved opportunities, ultimately enhancing the quality and effectiveness of professional development programs.